Human liver-resident CD56bright/CD16neg NK cells are retained within hepatic sinusoids via the engagement of CCR5 and CXCR6 pathways. (January 2016) - Hudspeth, Kelly; Donadon, Matteo; Cimino, Matteo; Pontarini, Elena; Tentorio, Paolo; Preti, Max; Hong, Michelle; Bertoletti, Antonio; Bicciato, Silvio; Invernizzi, Pietro; Lugli, Enrico; Torzilli, Guido; et al.
Abstract: Rationale: The liver-specific natural killer (NK) cell population is critical for local innate immune responses, but the mechanisms that lead to their selective homing and the definition of their functionally relevance remain enigmatic. Objectives: We took advantage of the availability of healthy human liver to rigorously define the mechanisms regulating the homing of NK cells to liver and the repertoire of receptors that distinguish liver-resident NK (lr-NK) cells from circulating counterparts. Findings: Nearly 50% of the entire liver NK cell population is composed of functionally relevant CD56 bright lr-NK cells that localize within hepatic sinusoids. CD56 bright lr-NK cells express CD69, CCR5 and CXCR6 and this unique repertoire of chemokine receptors is functionally critical as it determines selective migration in response to the chemotactic stimuli exerted by CCL3, CCL5 and CXCL16. Here, we also show that hepatic sinusoids express CCL3 pos Kupffer cells, CXCL16 pos endothelial cells and CCL5 pos T and NK lymphocytes. The selective presence of these chemokines in sinusoidal spaces creates a unique tissue niche for lr-CD56 bright NK cells that constitutively express CCR5 and CXCR6. CD56 bright lr-NK cells co-exist with CD56 dim conventional NK (c-NK) cells that are, interestingly, transcriptionally and phenotypically similar to their peripheral circulating counterparts. Indeed, CD56 dim c-NK cells lack expression of CD69, CCR5, and CXCR6 but express selectins, integrins and CX3 CR1. Conclusion: Our findings disclosing the phenotypic and functional differences between lr-Nk cells and c-NK cells are critical to distinguish liver-specific innate immune responses. Hence, any therapeutic attempts at modifying the large population of CD56 bright lr-NK cells will require modification of hepatic CCR5 and CXCR6. Highlights: Characterization of the mechanisms regulating the homing of NK cells to liver and the repertoire of receptors that distinguish liver-resident NK (lr-NK) cells from circulating counterparts (c-NK cells). Nearly 50% of the entire liver NK cell population is composed of functionally relevant CD56 bright lr-NK cells that localize within hepatic sinusoids. CD56 bright lr-NK cells express CD69, CCR5 and CXCR6 and this unique repertoire of chemokine receptors is functionally for their migration to hepatic sinusoids expressing their putative ligands. The selective presence of these chemokines in sinusoidal spaces creates a unique tissue niche for lr-CD56 bright NK cells that constitutively express CCR5 and CXCR6. This study releases the phenotypic and functional differences that distinguish lr-Nk cells from c-NK cells.